Ending hunger sustainably: Trends in official development assistance (ODA) spending for agriculture - Eber-Rose, Mali; Laborde Debucquet, David; Murphy, Sophia (International Institute for Sustainable Development, 2020)
This briefing note offers an overview of the trends in official financial disbursements to agriculture for the period 2002–2018. It offers an illustrative analysis of the types of exploration into public funding for development that can be conducted using a database maintained by OECD’s Development Assistance Committee (DAC).